1996
DOI: 10.1097/00043764-199608000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure of Water-Plant Operators to High Concentrations of Radon-222 Gas

Abstract: Water-plant operators may be exposed to high airborne radon-222 (222Rn) concentrations created when 222Rn gas transfers from water to air during the water treatment processes. To evaluate this hazard, we placed yearlong alpha-track radon detectors in 31 water plants. The geometric mean of the annual average airborne 222Rn concentrations was 3.4 pCi L-1 (126 Bq m-3), with a maximum of 133 pCi L-1 (4921 Bq m-3). We assessed the short-term temporal variability of 222Rn by monitoring four water plants continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…They found annual average radon concentrations ranging from 0.02 to 4.9 kBq·m −3 . In a small comparison of three workers monitored at work and at home, none had higher occupational exposures compared to home levels; however, Fisher et al (1996) concluded that employees working longer hours in some plant areas may accumulate exposures exceeding 4 WLM annually (32) .…”
Section: Resultsmentioning
confidence: 99%
“…They found annual average radon concentrations ranging from 0.02 to 4.9 kBq·m −3 . In a small comparison of three workers monitored at work and at home, none had higher occupational exposures compared to home levels; however, Fisher et al (1996) concluded that employees working longer hours in some plant areas may accumulate exposures exceeding 4 WLM annually (32) .…”
Section: Resultsmentioning
confidence: 99%
“…Trautmannsheimer et al, 2003;Nagels et al, 2009) or on basis of the local activity concentrations and the residence times (e.g. Fisher et al, 1996;Vaupotic, 2002;Marinko et al, 2004;Chmielewska et al, 2014;Stietka et al, 2014). Regarding possible, subsequent dose reduction measures, a determination of the local activity concentration is needed.…”
Section: Methodsmentioning
confidence: 99%
“…At facilities with a water treatment, there can be large diurnal variations depending on its operation mode, e.g. 222 Rn can outgas in large amounts during the backwash process of a filter (Fisher et al, 1996). In some of these cases, it is expedient to consider these diurnal variations of the activity concentration with separate measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations